Risk factors for acquisition of OXA-48-producing Klebsiella pneumonia among contact patients: a multicentre study. Issue 3 (March 2018) - Hilliquin, D.; Le Guern, R.; Thepot Seegers, V.; Neulier, C.; Lomont, A.; Marie, V.; Legeay, C.; Merrer, J.; Lepelletier, D.; Rogues, A.M.; Grandbastien, B.; Lucet, J.C.; et al.
Summary: Background: Cohorting carbapenemase-producing Enterobacteriaceae (CPE) carriers during hospitalization limits in-hospital spreading. Aim: To identify risk factors for CPE acquisition among contacts of an index patient in non-cohorted populations. Methods: A multicentre retrospective matched case–control study was conducted in five hospitals. Each contact patient (case) who acquired Klebsiella pneumoniae (KP)-OXA-48 from an index patient was compared to three contact (controls) with the same index patients matched with hospitalization in the same unit and similar exposure times. Findings: Fifty-one secondary cases and 131 controls were included. By univariate analysis, exposure time (odds ratio: 1.06; 95% confidence interval: 1.02–1.1; P  = 0.006), concomitant infection at admission (3.23; 1.42–7.35; P  = 0.005), antimicrobial therapy within the last month before hospitalization (2.88; 1.34–6.2; P  = 0.007), antimicrobial therapy during the exposure time (5.36; 2.28–12.6; P  < 0.001), use of at least one invasive procedure (2.99; 1.25–7.15; P  = 0.014), number of invasive procedures (1.52; 1.05–2.19; P  = 0.025), and geographical proximity (2.84; 1.15–7.00; P  = 0.023) were associated with CPE acquisition. By multivariate analysis, antimicrobial therapy during the exposure time (odds ratio: 6.36; 95% confidence interval: 2.46–16.44; P  < 0.001), at least one invasive procedure (2.92; 1.04–8.17; P  = 0.041), and geographical proximity (3.69; 1.15–11.86; P  = 0.028) were associated with acquisition. Conclusion: In this study, geographical proximity, invasive procedure, and antimicrobial therapy during exposure time were significantly associated with KP-OXA-48 acquisition.